Five years of improving diabetes control in Czech children after the establishment of the population‐based childhood diabetes register ČENDA. Issue 1 (16th October 2019) - Šumník, Zdeněk; Venháčová, Jitřenka; Škvor, Jaroslav; Pomahačová, Renata; Konečná, Petra; Neumann, David; Vosáhlo, Jan; Strnadel, Jiří; Čížek, Jindřich; Obermannová, Barbora; Petruželková, Lenka; Průhová, Štěpánka; et al.
Abstract: Objectives: The Czech National Childhood Diabetes Register (ČENDA) is a web‐based nationwide database that collects treatment and outcome data in children and adolescents with diabetes. Here, we present data from the first 5 years of ČENDA (2013‐2017). Methods: Data include characteristics of disease onset and annual summaries of key clinical care parameters from every patient treated by participating pediatric diabetes outpatient clinics. Results: The database contains data of 4361 children (aged 0‐19 years) from 52 centers (85% of all Czech pediatric patients). Of these, 94% had type 1 diabetes (T1D), 4.5% had genetically proven monogenic or secondary, and 1.5% had type 2 diabetes. In children with T1D, median glycated hemoglobin (HbA1c) decreased throughout the observed period from 66.3 to 61.0 mmol/mol ( P  < .0001, 95% confidence interval [CI] for change −5.6 to −4 mmol/mol). Consequently, the proportion of children reaching the target therapeutic goal of 58.5 mmol/mol increased from 28% in 2013 to 40% in 2017. The proportion of children treated with insulin pumps (CSII) remained stable over the observed period (25%). In a subanalysis of 1602 patients (long‐standing T1D diagnosed before 2011), the main predictors associated with lower HbA1c were treatment with CSII, male sex and care provided at a large diabetes center (>100 patients). Conclusions: A significant continuous decrease in HbA1c was observed in Czech children over the past 5 years. As this improvement was not accompanied by appreciable changes in the mode of therapy, we assume that the establishment of our nationwide register has itself constituted a stimulus towards improvement in the care process.